Prognostic impact of acute kidney injury following tricuspid transcatheter edge-to-edge repair. (3rd October 2022) - Tanaka, T; Kavsur, R; Sugiura, A; Galka, N; Oeztuerk, C; Vogelhuber, J; Becher, M U; Weber, M; Zimmer, S; Nickenig, G; Zachoval, C
Abstract: Background: A considerable risk of acute kidney injury (AKI) following transcatheter interventions without iodinated contrast agents has also been recognized; however, little is known about the incidence and clinical relevance of post-procedural AKI in patients undergoing transcatheter edge-to-edge repair (TEER) for tricuspid regurgitation (TR). Purpose: This study aimed to investigate the prognostic impact and predictors of post-procedural AKI following TEER for TR. Methods: We retrospectively analyzed 218 consecutive patients who underwent TEER for TR. Post-procedural AKI was defined as an increase in serum creatinine of ≥0.3 mg/dl within 48 hours or of ≥50% within seven days after the procedure, compared to baseline. Procedural success was defined as at least one grade reduction in TR severity upon discharge. We determined the association between post-procedural AKI and the composite outcome consisting of all-cause mortality and re-hospitalization due to heart failure within one year after the procedure. Results: Overall, the mean age of the patients was 79±7 years, and 46.3% of the patients were male. Post-procedural AKI occurred in 32 patients (14.7%) (Figure 1). Among baseline characteristics, male sex and an estimated glomerular filtration rate of <60 ml/min/m 2 were associated with the occurrence of AKI. In addition, patients without procedural success had a higher incidence of post-procedural AKI (30.4% vs. 1.8%; p=0.024). Patients with AKI had a higher incidence of in-hospital mortality compared to those without AKI (12.5% vs. 1.1%; p=0.005). Moreover, AKI was associated with the incidence of the composite outcome within one year after TEER for TR (adjusted hazard ratio: 2.06; 95% confidence interval: 1.11–3.84; p=0.023). In addition, our restricted cubic spline curve showed that a post-procedural increase in the creatinine level within seven days after the procedure was associated with a linear trend of the risk of the composite outcome after TEER (Figure 2). Conclusions: Post-procedural AKI occurred in 14.7% of patients undergoing TEER for TR, despite the absence of iodinated contrast agents, which was associated with worse clinical outcomes. Male sex and CKD at baseline were related to the occurrence of AKI, and the procedural success of TEER was associated with a lower incidence of AKI. Our findings highlight the clinical impact of AKI following TEER for TR and should help with identifying patients at high risk of AKI. Funding Acknowledgement: Type of funding sources: None.